Structure of a monoclinic polymorph of human carbonic anhydrase II with a doubled a axis - Robbins, Arthur H. (International Union of Crystallography, 2010)
The crystal structure of human carbonic anhydrase II with a doubled a axis from that of the usually observed monoclinic unit cell has been determined and refined to 1.4 Å resolution. The diffraction data with h = 2n + 1 were systematically weaker than those with h = 2n. Consequently, the scaling of the data, structure solution and refinement were challenging. The two molecules comprising the asymmetric unit are related by a noncrystallographic translation of ½ along a, but one of the molecules has two alternate positions related by a rotation of approximately 2°. This rotation axis is located near the edge of the central β-sheet, causing a maximum distance disparity of 1.7 Å between equivalent atoms on the diametrically opposite side of the molecule. The crystal-packing contacts are similar to two sequential combined unit cells along a of the previously determined monoclinic unit cell. Abnormally high final R (cryst) and R (free) values (20.2% and 23.7%, respectively) are not unusual for structures containing pseudo-translational symmetry and probably result from poor signal to noise in the weak h-odd data.